Vladi mir Golenishchev’s travel to Egypt in autumn and winter 1890–1891 (new archival evidence) - I. A. Ladynin (Шаги, 2023)
The publication presents a document preserved at the Archives of Vladimir Golenishchev in Paris (Centre Wladimir Golénischeff, École Pratique des Hautes Études). This is a report about the travel of the outstanding Russian Egyptologist Vladimir Golenishchev to Egypt that lasted from October 1890 to February 1891. It appears to be a preliminary version of a paper intended for submission to the Zapiski Vostochnogo otdeleniia Imperatorskogo Russkogo arkheologicheskogo obshchestva (Memoirs of the Oriental Department of the Imperial Russian Archaeological Society). The paper is kept in one file of red cardboard with pencil drafts, sketches and plans made by the Egyptologist during his travel. The report had not been published. It contains evidence about Golenishchev’s acquisitions for his collection (now at the Pushkin Museum of Fine Arts, Moscow; among the other things he purchased the papyri with the famous texts of Wenamun’s Voyage to Byblos and the Onomasticon of Amenemope), about the survey of archaeological monuments (most importantly, at the Kharga Oasis), about his new interpretations (the correct attribution of the so-called Hyksos sphinxes to Amenemhat III of Dynasty XII). Of special interest is the information about Golenishchev’s participation in the official reception in Egypt of the Russian heir apparent Nicholas Alexandrovich (future Emperor Nicholas II) and about some degree of tension between himself and the British officers in the Egyptian service, due to the contemporary confrontation of the Russian and the British Empire in the Great Game in the East.